2015
DOI: 10.7163/gpol.0019
|View full text |Cite
|
Sign up to set email alerts
|

Economic use of the Babia Góra Massif and the assessment of anthropogenic changes in the course of the timberline

Abstract: In Poland's Babia Góra Massif (the most elevated ridge in the Western Flysch Carpathians), and in the surrounding valleys, various kinds of economic use of natural resources have been engaged in the last 600 years or more. However, the most major changes in the natural environment here have taken place under the influence of grazing and forestry. Some such economic uses already represent forms of human activity that are now history, their cessation being the prerequisite for a regeneration of vegetation that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Certain studies have also reported that some parts of the timberline area are not as sensitive to climate change as others [32][33][34]. Particularly, many studies from abroad suggest that certain areas are much more sensitive to climate change than others [5].…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have also reported that some parts of the timberline area are not as sensitive to climate change as others [32][33][34]. Particularly, many studies from abroad suggest that certain areas are much more sensitive to climate change than others [5].…”
Section: Discussionmentioning
confidence: 99%